Pengaruh Metode Outdoor Study Terhadap Kecerdasan Ekologis Aspek Kognitif Peserta Didik Sekolah Dasar Adiwiyata kelas 5 Se- Kecamatan Laweyan - Ferdyan Rezka Rosyadah; Roy Ardiansyah (Universitas Sebelas Maret, 2025)
This study aims to examine the effectiveness of the outdoor study method in enhancing ecological intelligence in the cognitive aspect among fifth-grade elementary school students in Adiwiyata schools in Laweyan District. While outdoor learning is known to promote environmental awareness, its impact on cognitive ecological understanding remains underexplored in the elementary context. One experimental class used outdoor study as part of a quasi-experimental design, whereas the control class used traditional classroom instruction. The Wilcoxon signed-rank test, Mann-Whitney U test, and effect size calculation were used to examine the data, which were gathered utilizing pretests, posttests, and N-Gain analysis. The experimental group's posttest scores significantly outperformed the control group, according to the results, which also indicated a larger effect size and higher N-Gain score. These results imply that outdoor study enhances students' ecological cognitive abilities more than traditional approaches. However, successful implementation requires contextual learning activities and active engagement with the local environment. The study reinforces the importance of experiential learning in fostering meaningful understanding of environmental issues in early education.